Altitude, life expectancy and mortality from ischaemic heart disease, stroke, COPD and cancers: national population-based analysis of US counties. Issue 7 (15th March 2011) - Ezzati, Majid; Horwitz, Mara E M; Thomas, Deborah S K; Friedman, Ari B; Roach, Robert; Clark, Timothy; Murray, Christopher J L; Honigman, Benjamin
Abstract : Background: There is a substantial variation in life expectancy across US counties, primarily owing to differentials in chronic diseases. The authors' aim was to examine the association of life expectancy and mortality from selected diseases with altitude. Methods: The authors used data from the National Elevation Dataset, National Center for Heath Statistics and US Census. The authors analysed the crude association of mean county altitude with life expectancy and mortality from ischaemic heart disease (IHD), stroke, chronic obstructive pulmonary disease (COPD) and cancers, and adjusted the associations for socio-demographic factors, migration, average annual solar radiation and cumulative exposure to smoking in multivariable regressions. Results: Counties above 1500 m had longer life expectancies than those within 100 m of sea level by 1.2–3.6 years for men and 0.5–2.5 years for women. The association between altitude and life expectancy became non-significant for women and non-significant or negative for men in multivariate analysis. After adjustment, altitude had a beneficial association with IHD mortality and harmful association with COPD, with a dose–response relationship. IHD mortality above 1000 m was 4–14 per 10 000 people lower than within 100 m of sea level; COPD mortality was higher by 3–4 per 10 000. The adjusted associations for stroke and cancers were not statistically significant. Conclusions: Living at higher altitude may have a protective effect on IHD and a harmful effect on COPD. At least in part due to these two opposing effects, living at higher altitude appears to have no net effect on life expectancy.